OPTIMIZATION OF CHANNEL ASSIGNMENT FOR MOBILE COMMUNICATION USING TABU SEARCH - Loh, S.L.; Amat Ali, N.A.; Chong, S.H.; Malinin, D.; Fam, S.F. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Mobile communication is a process of exchanging information by connecting two parties through a wireless network. Practically, mobile communication system involves a large coverage area. However, there has only limited channels to accommodate all the users. Hence, with the increasing number of mobile users recently, it leads to channel assignment problem (CAP). To optimize the channel assignment problem, an initiative is taken to reuse the existing channels in an efficient way with the minimum interference occur in the channels assignment. This helps to optimize the usage of the channel assignment in mobile communication. Tabu Search (TS) technique is implemented to solve the CAP by searching for the global optimum solution with the minimum interference cost value. The reallocated channels are being analyzed on the value of the penalty cost based on the penalty cost function. The optimization of the channels assignment is a process of reducing total channels required as the solution is improved. An analytical analysis is carried out to investigate the effect of demand calls and the number of available channels on the cost value.